Characterization of the Erosion of Soft Tissue by Surgical Mesh In Vitro - SCHMIDT, AMANDA (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2021)
Surgical mesh implants have been extensively used in hernia treatment and pelvic organ procedures, such as organ prolapse and stress urinary incontinence. Since the onset of the use of such implants, major complications have been widely reported. Mesh erosion, where neighbouring tissues are worn from the rubbing of mesh, has been a concern in a significantly large number of clinical cases. However, there is still a lack in the literature on the mechanics of this occurrence. In this study, a purposely built apparatus was used to generate and measure the erosion of soft tissue (porcine muscle) by surgical mesh, and other products for comparison purposes. Three types of edge conditions were made from a typical knitted polypropylene mesh, scalpel cut, laser cut and hot-wire cut. Six stress urinary incontinence slings were tested: Gynecare with a mechanical cut edge, Gynecare with laser cut edge, Obtrix, Xxxxxx, Xxxxxx. In addition, a polypropylene sheet with serrations and a polypropylene suture were also tested. A close relationship was found between the roughness of the product?s edge and the rate of soft tissue erosion, though this was also affected by other factors such as the flexibility of the edge. A relationship between erosion and force applied was also demonstrated. From the tests carried out, results show that current commercially available meshes can erode through pelvic tissues in as little as a few weeks. Products advertised by companies as safer options, such as laser cut edges, produced the highest erosion rates. The specially knitted mesh slings (Xxxxxx and Xxxxxx), though apparently designed to avoid the problems with the knitted meshes, performed no better in the erosion tests. It was concluded that more research should be carried out on surgical mesh devices, and its risks should be well stated to patients.
APPROVED
Keywords: Surgical mesh; Erosion; Extrusion; Soft tissue; Muscle; Polypropylene